The Impact of Additive Manufacturing on the Innovation Process of the Sports Equipment Industry - Meier, Marlon (2017)
Fast changing customer demands and continuously rising requirements in product performance constantly challenge sports equipment manufacturers to come up with new and improved products to stay competitive. Therefore, the innovation process is an important key to the success of a company in the sports industry, as it determines the quality as well as the pace of new developed equipment. With the emerging technology of Additive Manufacturing, a new possibility to enhance this process became available for the industry. Creating shapes impossible for conventional processes, and that rapidly and economically, are only a few of its advertised benefits. Such a novelty in technology can significantly change the innovation process of the sports equipment industry. This research aims to analyse the current use of Additive Manufacturing technologies in the innovation process of the sports industry by investigating the companies’ level of awareness of this new technology, how it is implemented, and finally what impact it has on the innovation process. For this purpose, the work follows a qualitative research approach, generating findings through both, several case studies, as well a semi-structured interview with a sports equipment manufacturer. These findings are further discussed in the light of relevant academic literature with the help of an innovation matrix. The results of this work show, that the Additive Manufacturing process is still entering the sports equipment industry and has not become fully aware of yet. The technology provides several benefits when it comes to the innovation process, such as a faster development process, an optimised output, as well as the possibility to create new designs. However, Additive Manufacturing does not enhance the innovation process in a way that leads to new products and new markets. Limitations, including a small range of processable material and an inefficient mass production, still restrain the technology and lead to unused potential. Nevertheless, future prospects indicate the growing importance of Additive Manufacturing in the innovation process and show, that its advancement paves the way to new and innovative products.